Sunday

April 20, 2014

April 20, 2014

Posted by **olivia** on Monday, June 14, 2010 at 5:59pm.

- 9th grade -
**Reiny**, Monday, June 14, 2010 at 6:18pmyou could group it, then factor

ac-bc-ad+bd

= c(a-b) - d(a-b)

= (a-b)(c-d)

check it by expanding my answer.

**Related Questions**

Algebra 1 - Can anyone help me with these questions? Please 1. ac - bc + ad - bd...

Math - Show that (a^2+b^2)(c^2+d^2)=(ac+bd)^2 + (ad-bc)^2

Math - Show that (a^2+b^2)(c^2+d^2)=(ac+bd)^2 + (ad-bc)^2

Math - Show that (a^2+b^2)(c^2+d^2)=(ac+bd)^2 + (ad-bc)^2

Complex numbers - Prove algebraically that |w+z| is less than or equal to |w|+|z...

geometry - If (ad-bc)/(a-b-c+d)=(ac-bd)/(a-b+c-d) then prove that every portion ...

Physics, please help - Distruive interference? Unless you put C in the line ...

geometry - given that BD and AC are perpendicular, what is the length of Ac? AB=...

math - In a pentagon ABCDE, AB = AE, BC = ED and BD = EC. Prove that AC = AD.

math - prove the following: given: ABCD is a trapezoid with bases BC and AD to ...